Oncodomains: A protein domain-centric framework for analyzing rare variants in tumor samples - Peterson, Thomas A.; Gauran, Iris Ivy M.; Park, Junyong; Park, DoHwan; Kann, Maricel G. (PLOS Computational Biology, 2017)
Author summary The analysis of somatic variants in sequenced tumor samples is important for understanding the molecular disruptions that underlie the vast differences in individual cancer phenotypes or response to treatment. In order to understand which somatic mutations are functionally important for the initiation or progression of cancer, traditional analyses are ‘gene-centric’ in that they focus on single genes with high mutation frequency in tumor samples. However, many genes with experimental evidence of cancer involvement are found to be mutated in only a few tumor samples, hampering the data-driven identification of important genes. In our analysis, we leverage decades of important findings from structural genomics into the study of somatic variants by utilizing conserved protein domain families. Our method identifies ‘oncodomain hotspots’, sites within protein domain families with high mutation frequency in tumor samples. This enables our method to assess the importance of even rare variants by comparing to other genes with the same protein domain. By incorporating the structural and functional context encapsulated in protein domain families, we can identify even rare somatic variants in 5,437 genes, 3,041 of which are novel gene associations to cancer but are similar in structure and/or function to known cancer genes.